O MOVIMENTO NEGRO EDUCADOR E A FORMAÇÃO CONTINUADA DE PROFESSORAS/ES DA EDUCAÇÃO BÁSICA NO ESTADO DO ACRE: MULTIPLICADOS SOMOS MAIS FORTES - Maycon David de Souza Pereira (2023)
Taking into account that the Brazilian State confirms the existence of racism in national society and that Law 10.639/2003 appears as an advance in the fight against racism, the result of the anti-racist struggle of the Black Movement, determining the teaching of Afro-Brazilian history and culture and African education in Basic Education (BRASIL, 2003), making it essential to discuss an Anti-racist Education in the continuing education of teachers/es. This research is based on the premise that the Brazilian Black Movement is an educator, as it continues to produce other knowledge that emancipates and articulates studies on ethnic-racial issues in Brazil (GOMES, 2017). In view of this, this research has as a spatial cut the state of Acre, which makes up the set of 26 Brazilian states. In this sense, this research aims to analyze how the Black Educator Movement, in its work at the Federal University of Acre (Ufac), has promoted anti-racist training processes in the continuing education of basic education teachers in the state of Acre. Presenting as specific objectives: a) mapping the continuing education actions offered by the Black Educator Movement, in its work at the Federal University of Acre (Ufac) between 2013 and 2018; b) understand how the continuing education offered by the Black Educator Movement, in its work at the Federal University of Acre (Ufac) between 2013 and 2018, meets the educational policy of Education of Ethnic-Racial Relations, for the construction of an Anti-racist Education. C) verify the scope of continuing education offered by the Movimento Negro Educador in its work at the Federal University of Acre (Ufac) between 2013 and 2018. Theoretically based on Decoloniality, Cultural Studies, Ethnic and Racial Relations and the Critical Theory of society to think about contemporary society critically, among others. Its methodological process consists of the survey and study of bibliographic references, as well as conceptual and theoretical discussions; a documentary research is also carried out (LAKATOS; MARCONI, 2017) as a source of data collection, such documents are characterized as primary, written, official documents (because they are produced by people who represent an institution), with copies acquired after the request in public archive of the Núcleo de Estudos Afro-brasileiros e Indígenas of Ufac (Neabi/Ufac) of the final reports of the actions of continued formations, as well as public notices for these formative processes, in which the principles, objectives, number of enrolled, enrolled and graduating students, as well as the workload and curriculum for continuing education. By analyzing these documents, it was possible to conclude that the Black Educator Movement active at Ufac, between 2015 and 2018, promoted three continuous training processes aimed at teachers of the Basic Education network in the state of Acre, two of them at levels of specialization and one in the format of improvement, in addition to an extension project that also had a continuous training character aimed at this same public. These training processes covered seven cities in Acre, 172 teachers and 89 school units, which we consider indicative that this movement is moving towards structured racism in Brazilian society, highlighting the importance of inserting an Education from an anti-racist perspective in the continued training processes of teachers, in order to combat racism in the school environment, as well as in Brazilian society.